(untitled) (Biological Sciences - PJSIR, 2025)
The application of botanical pesticides has reported positive effects on increasing arthropod diversity indices in agriculture. This study aims to assess the effect of botanical insecticides from djengkol skin extract on arthropod diversity in shallot plantations in peatlands. This research was conducted on shallot plants on peatland with a randomised group design consisting of four treatments and repeated five times. The treatments consisted of three types of doses of djengkol skin extract, namely 0.125 Kg/ha, 0.25 Kg/ha, 0.375 Kg/ha and a control. This study focused on calculating the index of diversity, evenness, dominance and richness of arthropods. The results showed that the arthropod collection was 2743 heads consisting of Insecta comprises 9 orders (60 families), Arachnida with 1 order (9 families) and Diplopoda with 1 order (1 family). Application of botanical insecticides to shallot plantings on peatlands can increase the index of diversity, evenness, dominance and richness of arthropods.